COVID-19 infection in patients with acute leukemia; Istanbul experience - (:unkn) unknown (My University, 2021)
Coronavirus disease 2019 (COVID-19) has led to a global pandemic that has also challenged the management of various other life-threatening conditions, such as malignant disorders. In this study, we present the clinical features and treatment outcomes of twenty-seven COVID-19 positive patients with leukemia across seven different centers in Istanbul. From March 1st to December 31st 2020, 116 patients were diagnosed with acute leukemia. Thirty-two cases with acute lymphocytic leukemia (ALL), 82 cases with acute myeloid leukemia (AML), and 2 cases with mixed phenotype acute leukemia (MPAL) were identified. Of the 27 patients with the COVID-19 infection, seven patients had ALL, 19 patients had AML and one patient had MPAL. The mortality rate was 37% among the patients with AML, whereas there were no deaths in the ALL group. The mortality rate of AML patients with the COVID-19 infection was higher compared to cases without the infection (P<0.05). We could not detect any significant difference in the ALL cohort. This study, which includes one of the largest acute leukemia series in literature proved that acute myeloid leukemia patients with the COVID-19 infection have worse outcomes than patients without the infection. The high mortality among patients with acute leukemias hospitalized with COVID-19 highlight the need for aggressive infection prevention, increased surveillance and protective isolation and even modification of the therapy, in case of minimal residual disease (MRD) negativity.
Keywords: COVID-19; acute leukemia; acute lymphoblastic leukemia; acute myeloid leukemia; SARS-Cov2